PENGARUH GAMIFIKASI SHOPEE CAPIT TERHADAP CUSTOMER ENGAGEMENT, CUSTOMER EXPERIENCE, DAN CUSTOMER LOYALTY - Olivia Barcelona Nasution; Calvin Armando Rahadian (LPPM STIE YKPN Yogyakarta, 2022)
In this increasingly sophisticated and modern era has changed how various business run, one of them is selling and buying activities. Selling and buying activities nowadays can be done online from e-commerce platform. One of popular e-commerce in Indonesia is Shopee, where that platform apply gamification as the strategic to attract customers interest and keep customers loyalty. Gamification itself is the use of game elements but the context is not directly related to the game. This study aims to determine the effect of Shopee Capit gamification on customer engagement, customer experience, and customer loyalty. The type of this research is quantitative with 108 respondents from all over Indonesia. The data type that used is primary data through an online questionnaire with Google Form. The results of this research shows that gamification has positive and significant effect on customer engagement, customer experience, and customer loyalty.